Urban voters’ preference of issues in the general election: case study of Shah Alam parliamentary / Irwana Nooridayu Muhamad Hakimi and Shaharuddin Badaruddin - Muhamad Hakimi, Irwana Nooridayu; Badaruddin, Shaharuddin (Faculty of Administrative Science and Policy Studies, 2012)
Elections are important national events. It can also be regarded as the most critical contest at the national level and in the electoral system for every country. Currently, Malaysia is moving towards the 13th General Election which will be held in the year 2012. Elections after the Independence were held for 12 times from 1959 until 2008. From Independent Day in 1957, Selangor has been one of the strongholds for Barisan Nasional (BN) except in the 1969’s election. It was when The Alliance (known as Barisan Nasional today) held only 14 out of 24 seats in Selangor. Unfortunately for the first time during 12th General Election in 2008, Barisan Nasional (BN) was not able to continue their good performance since they only won 5 from 22 parliamentary seats in Selangor. This has caused a negative impact on Barisan Nasional (BN) at the State Legislative Assembly level because it only won 20 from 56 seats. In the 2008’s General Election, history was created in Selangor when Barisan Nasional (BN) was defeated by the opposition parties. Abdul Aziz B. Shamsuddin who represented Barisan Nasional in Shah Alam parliamentary area lost to Khalid B. Abd Samad who belonged to Parti Islam SeMalaysia (PAS). A study by Adam & Ferber (1980), finds that the voting trend of one particular area has a strong influence the on the effectiveness of issues delivered by a political party to the voters. Campbell et al. (1960) agree that political parties, current political issues and the candidate that are up for the election are the central factors that determine citizens’ vote choices. Therefore, this paper intends to determine the factor that influence Malay urban voters’ preference in an election from perspective of issues that happening around the people in Shah Alam parliamentary area. The areas are Kota Anggerik (N40) and Batu Tiga (N41) and the focus is on Malay urban voters. In collecting data process, cross-sectional survey to test the hypotheses and questionnaires been distributed to 324 Malay urban voters in Shah Alam.